Proposition d'un protocole de routage Geocast pour les UAVs - Mahi, Zohra; Bousbaa, Fatima Zahra (Université Amar Telidji - Laghouat - Département d'informatique, 2019)
Routing in cooperative Unmanned Aerial Vehicles (UAV)s networks is a challenging task due to high mobility of nodes, dynamically changing topology and 3-D movement. In this work, we study the fleet routing problem in Flying Ad-hoc Networks (FANET), which aims at delivering data to a specific group of mobile drones identified by their geographical location. Although many fleet routing protocols have been proposed, only partial inherent constraints of FANET (such as mobility, 3-D movement and reliability) are taken into account. Therefore, we propose a new geocast routing protocol namely Geocast routing protocol for fleet of UAVs (GeoUAVs) designed for satisfying military application. This protocol aims at delivering information to a specific group of mobile UAVs identified by their geographical location. It takes into account the mobility of nodes, dynamic changing topology with 3-D movement, and reliability. Simulations conducted in NS-3 simulator demonstrate that our proposal GeoUAVs outperforms AntHocNet and BeeAdHoc protocols by reducing the average delay and maximizing both the reliability and throughput.